"Now I just need something sweet": Racism, emotional eating, and health among African Americans. (January 2023) - Hoggard, Lori S.; Volpe, Vanessa V.; Hatton, Vanessa L.; Jones, Steven J.; Tikhonov, Aleksandr A.; Davis, Sarah E.
Abstract: Background: The Environmental Affordances Model theorizes that systemic racism disproportionately exposes African Americans in the United States to chronic everyday stressors (e.g., individual racism) while simultaneously shaping the availability of coping resources (e.g., fast food outlets) and engagement in self-regulatory strategies (e.g., emotional eating). Greater engagement in self-regulatory strategies is theorized to preserve mental health while contributing to medical morbidities and mortality. Objective: However, few studies have tested the Environmental Affordances Model, limiting our understanding of how the proposed pathways operate in the lives of African Americans. Methods: In the present study, the associations between systemic racism (institutional racism, cultural racism, neighborhood disadvantage), chronic everyday stressors (exposure to individual racism), emotional eating, and mental (anxiety symptomatology) and physical (self-rated overall physical health) health are assessed in a sample of 751 African Americans aged 18 to 88. Results: The path analysis reveals that institutional and cultural racism are both positively associated with individual racism. Neighborhood disadvantage is inversely associated with individual racism. Individual racism is significantly associated with greater anxiety symptomatology but is unrelated to self-rated overall physical health. Institutional and cultural racism are associated with emotional eating although individual racism and neighborhood disadvantage are not. Moreover, engagement in emotional eating exacerbates, rather than mitigates, the impacts of individual racism on anxiety symptomatology. Conclusions: We conclude that institutional and cultural racism contribute to individual racism experiences and emotional eating whereas emotional eating exacerbates associations among individual racism and anxiety symptomatology. Highlights: Systemic racism is associated with individual racism. Systemic racism (except for neighborhood disadvantage) relates to emotional eating. Individual racism is associated with anxiety symptoms but not emotional eating. Emotional eating moderates the link between individual racism and anxiety symptoms. Individual racism and emotional eating are unrelated to physical health.